SISTEM PENGENDALIAN INTERN PEMERINTAH DALAM PENGUKURAN KINERJA PEMERINTAHAN DI KABUPATEN BANDUNG - Yasmin Yasmin (Universitas Pakuan, 2018)
This paper studies and analyzes the implementation of Internal Control System of Government (SPIP) related to performance in Bandung regency, especially at district level. Descriptive is used as a research method with a qualitative approach. The result of this research is SPIP implementation in sub-district limited to SPIP internalization in all work process in organization, through five elements that is controlling environment, risk assessment, controlling activity, information and communication, and monitoring. Control environment not yet supported by commitment from leaders and all apparatus which can be seen from evaluation result of performance accountability system of government institution at sub-district in Bandung regency with average score obtained in CC criteria. Evaluation is performed on five major components of performance management including: Performance planning, Performance measurement, Performance reporting, Performance evaluation and Achievement of organizational goals/ performance. From assessment result, internal evaluation component becomes the smallest scoring contributor with almost 40% sub-districts are in the range of 2.00 to 4.00. Therefore the study resulted in the conclusion of the lack of consistent internal control application by the sub-districts, thus the commitment and the role of sub-district leadership to increase the role of the team of SPIP that has been established in the district.